Country Market Sequential Order-of-Entry: A Learning Effects Approach. Issue 4 (8th August 2017) - Azab, Carol; Key, Thomas Martin; Clark, Terry
ABSTRACT: In this article, we identify and describe the sequential order-of-entry problem. The sequential order-of-entry problem arises when, after having identified a desirable set of country markets to enter, firms are unable (because of budgetary constraints), or unwilling (because of possible learning or strategic issues), to enter all at once. The question then arises whether some sequences to entering the desirable set of country markets are better than others? Answering this question is shown to be nontrivial. The article outlines a number of arguments for the existence of superior sequences to entering a set of desirable country markets, and develops normative and dynamic frameworks to aid in the identification and evaluation of sequences.